The Schwarzbein principle II : the transition : a regeneration process to prevent and reverse accelerated aging / Diana Schwarzbein, Marilyn Brown - Schwarzbein, Diana
Heal or improve your metabolism; lose excess fat weight; prevent and reverse the degenerative diseases of aging; achieve your ideal body composition; stop chronic dieting and eliminate cravings and addictions.